Emerging industries: institutions, legitimacy and system-level agency. Issue 4 (3rd April 2022) - Gong, Huiwen; Binz, Christian; Hassink, Robert; Trippl, Michaela
ABSTRACT: Economic geographers have studied emerging industries in regions from various perspectives, such as life cycle, evolutionary economic geography and systemic approaches. However, so far they have insufficiently conceptualized the effects of institutional structures on new industry emergence. This special issue on 'Emerging Industries: Institutions, Legitimacy and System Building' therefore shows recent work that seeks to advance the analysis of emerging industries by drawing on institutional approaches. The present introductory article identifies key characteristics of 'emerging industries', establishes a heuristic for the conceptualization of the institutional dynamics in emerging industries, applies it to the special issue papers and outlines a future research agenda.